Precipitation Reactions in Nickel—Hydrogen System: ab initio Study - Teus, S.M. (Металлофизика и новейшие технологии, 2016)
A type of precipitation reactions in the nickel—hydrogen system is studied by means of first-principle atomic calculations. The concentration dependence of solution enthalpy is calculated, and its second derivative is shown to be negative within the hydrogen-to-nickel ratios, H/Ni, of 0.03—0.75. This result suggests that a spinodal decomposition of the solid solution occurs resulting in formation of the hydrogen-rich and hydrogen-depleted phases. The obtained hydrogen concentrations in these conjugated phases are in consistency with the available experimental data. The effects of hydrogen concentration on the electronic structure and its correlation with thermodynamic stability of phases confirm that spinodal decomposition in the nickel— hydrogen system has the electronic origin. The obtained results are at variance with the widely accepted concept of the nickel hydride.